2018
DOI: 10.1002/anie.201809689
|View full text |Cite
|
Sign up to set email alerts
|

NiFe Hydroxide Lattice Tensile Strain: Enhancement of Adsorption of Oxygenated Intermediates for Efficient Water Oxidation Catalysis

Abstract: The binding strength of reactive intermediates with catalytically active sites plays a crucial role in governing catalytic performance of electrocatalysts. NiFe hydroxide offers efficient oxygen evolution reaction (OER) catalysis in alkaline electrolyte, however weak binding of oxygenated intermediates on NiFe hydroxide still badly limits its catalytic activity. Now, a facile ball‐milling method was developed to enhance binding strength of NiFe hydroxide to oxygenated intermediates via generating tensile strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
218
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(230 citation statements)
references
References 42 publications
(16 reference statements)
12
218
0
Order By: Relevance
“…Conceivably, the exchange of ligand and hydroxide in the electrolyte was confirmed by the analysis of UV absorption spectra of the electrolyte of the immersion FN‐2 (Figure S9, Supporting Information). As shown in Figure S10 in the Supporting Information, after soaking in KOH solution, the FN‐2 powder exhibits obvious peaks at 11.5°, 23.3°, 34.5°, and 60.3°, which can be assigned to NiFe‐LDH, indicating that the vast majority of FN‐2 are transformed to NiFe‐LDH . We did the same experiment for Ni‐MOFs and Fe‐MOFs as FN‐2, and got a similar result (Figure S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 53%
“…Conceivably, the exchange of ligand and hydroxide in the electrolyte was confirmed by the analysis of UV absorption spectra of the electrolyte of the immersion FN‐2 (Figure S9, Supporting Information). As shown in Figure S10 in the Supporting Information, after soaking in KOH solution, the FN‐2 powder exhibits obvious peaks at 11.5°, 23.3°, 34.5°, and 60.3°, which can be assigned to NiFe‐LDH, indicating that the vast majority of FN‐2 are transformed to NiFe‐LDH . We did the same experiment for Ni‐MOFs and Fe‐MOFs as FN‐2, and got a similar result (Figure S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 53%
“…Unfortunately, weak binding of oxidized intermediates on NiFe hydroxide still limits its catalytic activity. Hence, Sun and co‐workers design a simple ball milling method to increase the binding strength of NiFe hydroxide and oxygen‐containing intermediates by generating tensile strain, thereby reducing the antibonding filling states in the d orbital and thus promoted oxygenated intermediates adsorption 41. The NiFe hydroxide having an increased tensile strain after ball‐milling exhibits an OER onset potential as low as 1.44 V (vs RHE) and only an overpotential of 270 mV was required to reach a water oxidation current density of 10 mA cm −2 .…”
Section: Ni/fe‐based Micro/nanostructures For Electrochemical Water Omentioning
confidence: 99%
“…These features will guarantee the efficient OER process under high current conditions for industrial applications. Recently, Liu's group reported that generating the lattice strain of NiFe hydroxide can effectively enhance the binding strength between NiFe hydroxide and oxygenated intermediates . From another side, electronic engineering is also crucial to enhance the electrocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%